Manufacturing systems used in the shipbuilding industry from years 2000 up to nowadays - Czifra, György (Національний технічний університет "Харківський політехнічний інститут", 2024)
The continuous growth in demands for product quality and their utility properties in today's competitive environment places increased requirements on activities ranging from pre-production stages to sales completion. From these facts, it is evident that special attention must be paid to material selection, product design, and the construction of individual components, as well as the technologies used in their production and processing. Achieving high technical parameters for products while simultaneously optimizing the cost/performance or cost/utility value ratio compels designers and engineers to explore new progressive materials with high mechanical, chemical, and physical properties.

Безперервне зростання вимог до якості продукції та її корисних властивостей у сучасному конкурентному середовищі висуває підвищені вимоги до промисловості, починаючи від етапів підготовки виробництва до його завершення і продажів. З цих фактів видно, що особлива увага повинна бути приділена вибору матеріалів, дизайну виробів і конструкції окремих компонентів, а також технологіям, що використовуються при їх виробництві та обробці. Досягнення високих технічних параметрів виробів з одночасною оптимізацією співвідношення витрат і продуктивності або витрат і корисностей змушує конструкторів та інженерів досліджувати нові прогресивні матеріали з високими механічними, хімічними та фізичними властивостями.
Виробничі системи, які використовуютьсяу суднобудівній промисловості від 2000 року до сьогодення
Keywords: shipbuilding; manufacturing systems; artificial intelligence; material selection; product design; construction of individual components; суднобудування; виробничі системи; штучний інтелект; асортимент продукції; автоматизована виробнича лінія